Analysis of the Significance of Perceived Meaningfulness in Determining the Strategic Position of the "Achieve Art Space" Art Gallery Destination in Yogyakarta - Nanda Litausi’i Rizqina; Raden Roro Ratna Roostika (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this study is to examine and evaluate the impact of destination image and destination quality on perceived meaningfulness and intention to return to Yogyakarta's "Achieve Art Space" art exhibition. Purposive sampling was used in this study's sample selection, with 275 respondents taking part in the study. This study used Structural Equation Modeling (SEM) using the SmartPLS version 3.0 software for statistical analysis. The findings of this study's data analysis show that destination quality has a positive and significant effect on destination image. The perceived meaningfulness of a place is positively influenced by its quality and image. Furthermore, destination quality, destination image, and perceived meaningfulness all have a positive and significant impact on the desire to visit again.